Pengaruh Tarif Kamar dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan pada Horison Hotel Semarang - Rifky Adhitya; Rodhiyah Rodhiyah; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2015)
HORISON HOTEL is one of company that moves in side of hospitality at Semarang. Some problems are captured lack of pieces overnight rates, maximal service and facilities at the hotel This purpose to determine influence of Room Rates, Service Quality, Customer Satisfication  to Customer Loyalty. Type of research used is explanatory with 100 sample respondents (purposive effect). Analysis of the data used is qualitative and quantitative, qualitative analysis tools such as categorization and quantitative analysis tools such as the coefficient of determination, t test, F test and path analysis.The results and discussion of room rates are very low (70%), quality of service is very good (61%), customer satisfaction is very high (78%) and very high customer loyalty (67%). There is a positive and significant influence between room rates for customer satisfaction (14.4%), a positive and significant influence between room rates on customer loyalty (20.6%), a positive and significant effect of service quality on customer satisfaction (13%), positive and significant impact of service quality on customer loyalty (81.1%) and there is a positive and significant impact of customer satisfaction on customer loyalty (12.8%).Conclusion There are significant effect between room rates and quality of service to customer satisfaction (18.5%) and a significant influence between the influence of room rates, service quality on customer loyalty through customer satisfaction (81.2%). Advice can be given include: repair of all equipment in the room were not functioning as it should, repairing all kinds of facilities, to fully leverage with both the employees and officers, and the effort required to provide discounted hotel rates stay more especially on particular days.